Evaluating the impact of judicial mediation on access to justice: Perspectives from the Singapore State Courts' Judicial mediation system - QUEK ANDERSON, Dorcas (Institutional Knowledge at Singapore Management University, 2017)
Mediation and other alternative dispute resolution (ADR) processes have been increasingly relied on by many courts to increase access to justice and to mitigate the limitations of the formal adjudicatory system. ADR is seen as providing a form of “informal justice” that is more empowering and participatory, while also less alienating and costly. Against this backdrop, judicial mediation has emerged as an additional ADR option. Judicial mediation programs have emerged in varying forms – ranging from a trial judge mediating the dispute before trial, to having a dedicated judge mediate a dispute without hearing the trial – and with mixed reviews. The Quebec judicial mediation program has been described as heralding a new participant-centred normative order that is better adapted to the needs of the parties. On the other hand, judicial mediation programs within some parts of China have been criticised as being fraught with internal contradictions.This paper focuses on appraising the judicial mediation model against the benchmark of increasing access to justice. The broader issue that will be explored is whether judicial mediation enhances access to justice more than other types of mediation programs, or conversely, whether it detracts from the promotion of access to justice. These issues are discussed with reference to the judicial mediation model that has been used in the Singapore State Courts. The paper argues that judicial mediation is most consonant with the broadening concepts of justice as well as the role of the courts, which are increasingly gaining traction globally. When designed with appropriate safeguards and contextualised to fit the societal preferences of the relevant jurisdiction, a judicial mediation program has immense potential to enhance access to justice. The current judicial mediation system in the Singapore State Courts illustrates the many benefits to be reaped from such a program, as well as some of the pitfalls that should be averted.